QRIS in the NTB tourism industry: Unified Theory of Acceptance and Use of Technology (UTAUT) model - Suwardi, Didi; Suharti; Aprirachman, Rozzy (Universitas Merdeka Malang, 2025)
Rapid technological growth has significant increased in Indonesia. This development has driven the expansion of internet-based innovations, particularly in the financial technology (fintech) sector, which promotes digital payment systems to enhance efficiency, accessibility, and convenience. This study aims to examine the factors influencing the adoption and use of the Quick Response Code Indonesian Standard (QRIS) among tourism industry players in Nusa Tenggara Barat (NTB), as well as to formulate effective strategies to enhance its utilization. This study using quantitative methods, focus on statistical analysis to determine the correlation between various factors and QRIS adoption rates among tourism industry stakeholders in NTB. The quantitative analysis utilized Structural Equation Modeling (SEM) based on the Unified Theory of Acceptance and Use of Technology (UTAUT) framework, which comprises six key constructs including Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Behavioral Intention, and Use Behavior. Data were collected from 101 respondents selected through proportionate random sampling, representing various sectors of the tourism industry, including travel agencies, hotels, restaurants, bars, spas, and diving operators. The empirical results demonstrate that Behavioral Intention has a significant positive effect on Use Behavior These findings indicate that perceptions of usefulness, ease of use, and supporting conditions are the primary determinants of QRIS adoption, whereas social factors have limited influence in this context. Based on the findings, several strategic recommendations are proposed to enhance QRIS adoption among NTB tourism industry players, including strengthening awareness and user education, improving infrastructure and technical support, fostering institutional partnerships, and providing targeted incentives to encourage sustained utilization.